Transmission of pLVPK-like virulence plasmid in Klebsiella pneumoniae mediated by an Incl1 conjugative helper plasmid - Xuemei Yang; Miaomiao Xie; Qi Xu; Lianwei Ye; Chen Yang; Ning Dong; Edward Wai-Chi Chan; Rong Zhang; Sheng Chen (iScience, 2022)
Summary: We previously reported the recovery of five ST11 carbapenem resistant hypervirulent Klebsiella pneumoniae (CR-HvKP) strains that harbored pLVPK-like virulence plasmids, yet molecular mechanisms underlying acquisition of virulence plasmid by ST11 K. pneumoniae have not been characterized. In this study, we showed that virulence plasmids in these CR-HvKP strains could be transferred to Escherichia coli strain EC600 via conjugation. Transmission of the virulence plasmids was found to involve formation of fusion plasmids with an Incl1 type conjugative plasmid and a small ColRNAI plasmid through homologous recombination and by insertion sequences IS26 and IS903B. The conjugative fusion event would transform different ST types of K. pneumoniae, in particular, the clinically prevalent ST11 or ST258 CRKP into CR-HvKP. Clinical factors that promote or suppress the occurrence of this fusion process should be further investigated to devise new approaches to halt such bacterial evolution trends.